Hits & misses : stories - Rich, Simon (Little, Brown and Company, 2018)
A hilarious collection inspired by a former Saturday Night Live writer's real experiences in Hollywood, chronicling the absurdity of fame and the humanity of failure in a world dominated by social media influencers and reality TV stars.